Entrepreneurial Marketing and Consumer Need Adaptability for Strengthening Market Penetration Power in MSMEs FnB Sector Within Central Java - Ali, Ahmad; Nurcahyo, Satria Avianda; Widagdo, Teguh Harso (BISNIS, 2025)
This study aims to analyze the influence of entrepreneurial marketing and consumer needs adaptability in strengthening market penetration among Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage (FnB) sector in Central and East Java. The research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). A total of 150 FnB MSME owners and managers were selected through purposive sampling. The findings indicate that entrepreneurial marketing has a significant and positive effect on marketing performance and market penetration. Consumer needs adaptability is proven to mediate the relationship between entrepreneurial marketing and marketing performance, highlighting the importance of aligning innovation with consumer expectations. Furthermore, the integration of aesthetic value in product presentation enhances consumers’ emotional engagement, which indirectly supports market penetration. The results also reveal that adaptability and creativity are not only strategic capabilities but are culturally embedded practices within local MSMEs. This study concludes that FnB MSMEs can achieve sustainable growth by adopting entrepreneurial-oriented marketing strategies that are responsive to dynamic consumer preferences, local tastes, and aesthetic values, thereby improving market expansion and overall marketing performance in a competitive and evolving business environment.